2007
DOI: 10.1167/iovs.06-0641
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Profiling of the Retinoschisin-Deficient Retina in Early Postnatal Mouse Development

Abstract: The findings imply that microglia/glia activation may be triggering events in the photoreceptor degeneration of retinoschisin-deficient mice. Furthermore, the data point to a role of Erk1/2-Egr1 pathway activation in RS pathogenesis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 55 publications
2
60
0
1
Order By: Relevance
“…We have previously detected high Egr1 transcript levels (Gehrig et al 2007) and reactive microglia in the degenerating retina of retinoschisin-deficient mice (Weigelt et al 2007). To verify these findings and to identify a potential connection between both events, we monitored Egr1 gene expression in Rs1h -/Y retinas by quantitative real-time RT-PCR.…”
Section: Induced Egr1 Mrna and Protein Expression In Activated Rs1h -mentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously detected high Egr1 transcript levels (Gehrig et al 2007) and reactive microglia in the degenerating retina of retinoschisin-deficient mice (Weigelt et al 2007). To verify these findings and to identify a potential connection between both events, we monitored Egr1 gene expression in Rs1h -/Y retinas by quantitative real-time RT-PCR.…”
Section: Induced Egr1 Mrna and Protein Expression In Activated Rs1h -mentioning
confidence: 96%
“…Several attempts to identify transcriptomic markers of these molecular activation pathways have been made by large scale gene expression profiling in several animal studies (Ahmed et al 2004;Chen et al 2004;Steele et al 2006;Vazquez-Chona et al 2004). Related to this, highly activated neurotoxic microglia cells and a strong overexpression of early growth response (Egr) 1 has recently been described in the retina of retinoschisin-deficient (Rs1h -/Y ) mice (Gehrig et al 2007), a murine model of human X-linked juvenile retinoschisis (Weber et al 2002).…”
Section: Introductionmentioning
confidence: 93%
“…To identify novel genes involved in the activation of microglia, we have previously performed DNA-microarray analysis of isolated retinal microglia from degenerating Rs1h 2/Y and wt retinas (24,28,30 For a more precise refinement of the temporal expression profile of AMWAP in relation to the inflammatory process, mRNA levels were quantified in retinal tissue of postnatal stages (P)11, 12, 14, 18, 21, 24, and 28 (Fig. 1B).…”
Section: Amwap Is Strongly Induced In Activated Retinal Microgliamentioning
confidence: 99%
“…However, excessive or prolonged microglial activation in the CNS and the retina can lead to chronic inflammation with severe pathological side effects often resulting in irreversible neuronal loss (2,20,21). In eye research, various animal models have demonstrated that microglial activation is tightly associated with and mostly precedes retinal degeneration and photoreceptor apoptosis (22)(23)(24). Functional and phenotypic characterization of microglia populations in the diseased retina could be of high relevance to reveal signaling events that trigger their activation.…”
mentioning
confidence: 99%
“…Unsere Arbeitsgruppe konnte die zeitliche Verbindung der Mikrogliaaktivierung mit der Photorezeptorapoptose bei Retinoschisin-defizienten (Rs1h-/Y) Mäu-sen untersuchen, einem Modell für die X-gebundene Retinoschisis [65]. Dabei konnten DNA-Mikroarrays zeigen, dass die transkriptionelle Reaktion von Mikroglia dem Zelltod in der Netzhaut zeitlich deutlich vorausgeht [21]. Die frühe Mikrogliose steht auch in direktem Zusammenhang mit der Netzhautdegeneration im Fam161-defizienten Mausmodell der Retinitis pigmentosa [33,42].…”
Section: Mikroglia Bei Mausmodellen Erblicher Netzhautdystrophienunclassified